2002
DOI: 10.1242/jcs.115.13.2757
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic crosstalk of TNF receptors: TNF-R2-induces depletion of TRAF2 and IAP proteins and accelerates TNF-R1-dependent activation of caspase-8

Abstract: We have recently shown that stimulation of TNF-R2 selectively enhances apoptosis induction by the death receptor TNF-R1. Here, we demonstrate that stimulation of CD30 or CD40 also leads to selective enhancement of TNF-R1-induced cell death. Enhancement of apoptosis was correlated with the depletion of endogenous TRAF2 within 1 to 6 hours. Selective prestimulation of TNF-R2 for several hours inhibited TNF-R2-induced activation of the anti-apoptotic NF-κB pathway up to 90% and dramatically enhanced apoptosis ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(33 citation statements)
references
References 56 publications
1
31
0
1
Order By: Relevance
“…The default signaling pathway of TNFA-Rs is cell survival in a process regulated by TNF Receptor Associated Factor 2 (TRAF2) [ 42 ]. Continuous activation of either of the two TNFA-Rs, such as during aberrant inflammation, can incur a TRAF2 deficiency that disrupts negative regulation of the death domains associated with TNFA-R1, thereby leading to death pathway signaling [ 43 ]. We predict that CCHFV replication and extensive TNFA-R activation consumes TRAF2 in both hepatocytes and Kupffer cells, subsequently driving signaling pathways towards cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The default signaling pathway of TNFA-Rs is cell survival in a process regulated by TNF Receptor Associated Factor 2 (TRAF2) [ 42 ]. Continuous activation of either of the two TNFA-Rs, such as during aberrant inflammation, can incur a TRAF2 deficiency that disrupts negative regulation of the death domains associated with TNFA-R1, thereby leading to death pathway signaling [ 43 ]. We predict that CCHFV replication and extensive TNFA-R activation consumes TRAF2 in both hepatocytes and Kupffer cells, subsequently driving signaling pathways towards cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been found that the signaling outcome of different TNFR1-mediated pathways can be modulated by TNFR2. For instance, activation of TNFR2 can lead to a significant depletion of cytosolic TRAF2-cIAP1/2 complexes, thus switching the TNFR1-mediated signaling to cell death 72 . We speculate that the differences in TNFR1 and TNFR2’s responds to membrane-bound and soluble ligands are resulted from the conformational dynamics of the two receptors, which further affects the kinetics of their ligand binding and clustering.…”
Section: Resultsmentioning
confidence: 99%
“…A possible reason for cIAP1/TRAF2-depletion in macrophages could be signaling through TNFR2 [ 39 ]. Oligomerized TNFR2 recruits TRAF2 along with TRAF1 and cIAP1/2, leading to NF-κB activation, but also depletes TRAF2-cIAP1/2 complexes in the cytoplasm [ 40 , 41 ]. The largely TNF-independent cIAP1/TRAF2-depletion in our system however pointed to a TNFR2-independent mechanism.…”
Section: Discussionmentioning
confidence: 99%